Perforation from endoscopic small bowel biopsy. Issue 1 (January 1993) - Scott, B; Holmes, G
Abstract : Two patients, having undergone an apparently straightforward endoscopy with small bowel biopsy, developed a perforation. One, who proved to have normal small bowel mucosa, needed laparotomy and suturing of the duodenal perforation. The other, who had coeliac disease, settled with conservative management.